Polymorphisms of human leukocyte antigen B*27 on clinical phenotype of spondyloarthritis in Chinese - Ma, Hai‐Jun (J Clin Lab Anal, 2017)
BACKGROUND: In recent years, an ever‐increasing number of alleles of human leukocyte antigen B*27 (HLA‐B*27) have been identified. This study aimed to establish an updated method for HLA‐B*27 subtyping, and to investigate the impact of HLA‐B*27 polymorphisms on the clinical phenotype of spondyloarthritis (SpA). METHODS: Overall, 184 SpA patients were recruited for analyzing diversity of HLA‐B*27 via an updated high‐resolution polymerase chain reaction amplification with sequence specific primers (PCR‐SSP). RESULTS: The prevalence of HLA‐B*27 was 94.0%, and four subtypes were identified including HLA‐B*2704 (77.5%), B*2705 (20.2%), B*2707 (1.7%), and B*2724 (0.6%). There was an obvious male predominance (P=.05) and markedly elevated C‐reaction protein (CRP) in B*27 positive SpA (P<.01). In multivariate linear regression analysis, the elevated CRP was positively associated with HLA‐B*27 positivity (regression coefficient B=46.1, P=.0003), grade of sacroiliitis (B=47.5, P=.0032), and male gender (B=20.4, P=.0041). Notably, a male predilection was also found in B*2705 positive SpA while B*2707 was associated with older age, higher positive family history, and higher prevalence of extra‐articular features (all P<.05). CONCLUSIONS: In this study, an updated PCR‐SSP technique to identify increasing alleles of HLA‐B*27 was developed and their different effects on clinical manifestations of SpA were demonstrated. Genotyping of HLA‐B*27 would shed light on our understanding of the pathogenesis of SpA.